Oroileal transit of slow release 5-aminosalicylic acid. Issue 5 (May 1993) - Goebell, H; Klotz, U; Nehlsen, B; Layer, P
Abstract : The predominant active anti-inflammatory moiety in chronic inflammatory bowel disease is 5-aminosalicylic acid (5-ASA). As unprotected 5-ASA is rapidly absorbed in the upper gastrointestinal tract several slow release preparations have been developed to permit passage of 5-ASA to the lower small bowel and to the colon. To investigate luminal kinetics and extent of the release of 5-ASA intraluminal concentrations and loads of this compound together with that of its main metabolite acetyl-5-aminosalicylic acid (ac-5-ASA) were studied, over 15 hours after giving the slow release preparation Salofalk at a dose of 500 mg orally together with a test meal. Plasma concentrations and urinary excretion were also measured. Six healthy volunteers swallowed an 11 lumen oroileal tube, which allowed marker perfusion, aspiration of luminal content from the duodenum, mid-jejunum, and ileum, and recording of intestinal motility. Emptying of 5-ASA into the duodenum started after emptying of the meal, together with the first phase III of interdigestive motility. Mean luminal concentrations of 5-ASA and ac-5-ASA increased continuously from duodenum (both: 15 to 30 micrograms/ml) to ileum (60 to 110 micrograms/ml and 80 to 150 micrograms/ml respectively) over three hours and decreased over the next three hours. During 10 hours after eating, 30% of the total dose passed the ileum in solution and another 10% were excreted in urine. Thus about 60% reached the colon unreleased from tablets and another 30% were in solution. The ratio of 5-ASA and ac-5-ASA in solution was about 1:1 in the duodenum and 1:1.5 to 1:2 in the more distal small intestine. The data suggest that the large quantities of intraluminal ac-5-ASA are generated in the intestinal mucosa and reach the lumen by back diffusion. The results show that most of the 5-ASA from this slow release preparation is delivered into the colon, which explains its effectiveness in ulcerative colitis. The considerable luminal concentrations already present in the distal ileum might justify therapeutic trials in Crohn's disease.